Using Wordwall Media to Improve Student Learning Outcomes in English Language Learning for Nursing Students - Fidian, Athia (Lingustic, Literature and English Education, 2023)
This research aims to see the influence of wordwall interactive learning media on improving English learning outcomes for nursing students at Universitas Muhammadiyah Magelang. This research is quantitative research with a pre-experimental design method analyzed using Wilcoxon. D3 nursing students from Universitas Muhammadiyah Magelang are the population of this study. The independent variable in this research is the interactive learning media Wordwall, while the dependent variable is the learning outcomes of nursing students. The research results obtained were Asymp. Sig. (2-tailed) is 0.000 which is smaller by 0.05. This shows that there is a significant difference between the pre-test and post-test scores. So, it can be concluded that the use of interactive learning media Wordwall can improve nursing student learning outcomes. Keywords: Wordwall, Interactive Learning Media, English Learning, English Learning Outcomes.